The role of the number of transparent covers in enhancing the efficiency of flat plate collectors - Khaled, Amer; Elzer, Rahma; Alkhazmi, Ali (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
Solar energy has gained traction as an eco-friendly alternative to combat Carbon dioxid (CO2) emissions from fired-fossil fuel electrical power plants. One common application is converting solar energy into heat for water heating systems, often achieved through flat-plate solar heating collectors. The usefull thermal energy of these collectors depends on factors like climate, design, and operational parameters. This study examines the effect of number of transparent covers (TCs) and the inlet water temperature on the performance of a liquid-flat plate solar collector (LFPSC) in Beida city, Libya, on July 21, 2020, with data collected at hourly intervals. Different scenarios were considered, varying the number of covers (ranging from 0 to 3) and the inlet water temperatures (ranging from 25°C to 50°C). The findings reveal that the optimal number of covers is influenced by multiple factors, not solely the prevailing climatic conditions. Inlet water temperature and the collector's length were identified as the most influential parameters affecting the over all performance of LFPSC. Consequently, the decision to employ a specific number of covers depends on the system's operating conditions. When the inlet water temperature matches the ambient temperature, a single cover suffices for optimal collector performance. However, if the inlet water temperature surpasses the ambient temperature, multiple covers are necessary to achieve the collector's peak efficiency. This research underscores the importance of considering various factors, beyond just climate, when designing and operating solar collectors for efficient water heating systems.